ABOUT THEORETICAL AND METHODOLOGICAL ISSUES OF GEOECOLOGY (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Based on different authors and own research results, interpretations and reasoning the theoretical bases of Geoecology and its scientific problems are analyzed and as well as some methodological fundamentals are suggested and justified for Geoecology.
Keywords: geoecology; methodology; methodological issues; science